FOSTERING QUALITATIVE CONTENT ANALYSIS SKILLS THROUGH CASE METHOD - Noermanzah Noermanzah; Dian Eka Chandra Wardhana; Awalludin Awalludin (English Review: Journal of English Education, 2022)
This study is aimed at demonstrating how students in the University of Bengkulu's master's program in Indonesian language education have improved their capacity to employ qualitative content analysis techniques. This study uses a classroom action research method with the Kemmis and MC model. Data collection techniques using observation, interviews, tests, and documentation. Data analysis techniques are: 1) analyzing qualitative data, namely observation data, interviews, and document analysis; 2) analyzing quantitative data, namely performance test data, and 3) interpreting and setting indicators of success of actions. Test the validity of the data using the technique of inter rater, member check, and triangulation of data sources. The results showed that the application of case method carried out online through Zoom Cloud Meetings and LMS University of Bengkulu was able to improve the ability to use qualitative content analysis methods for students. Improvement both in terms of the learning process that activates the learning experience through solving discourse analysis cases at the level of knowledge and activities trying to analyze class discourse, as well as increasing learning outcomes in the first cycle by 16% which reached a value of 80, increasing in cycle 2 by 91.66% which reaches a value of 80.